Mitigasi deforestasi: Sosialisasi daur ulang kertas pada mahasiswa UIN Maulana Malik Ibrahim Malang - ’Adhim, Rizka Maziyyah (Maliki Interdisciplinary Journal, 2024)
Indonesia’s land covers 191,357,868 with 62.97% of the forest area producting trees as the most sought-after paper- making raw material. Indonesian pulp and paper industry is one of the 3rd largest paper manufacturers in the world. The surge in paper demand is not comparable to the available raw materials. If this is left behind, then deforestation or massive depletion of forest land can occur. Preventing this, disaster mitigation as a preventive effort can be done through the cultivation of character caring for its primary environment at the educational level. The research uses context analysis methods by gathering various research sources to obtain theories as a reference for writing, and methods of socialization of paper recycling processing in UIN student Maulana Malik Ibrahim Malang. Socialization results show that creative and innovative waste management is needed to reduce the volume of paper waste, by recycling the waste. They feel helped by the innovation, so that papers that are usually just thrown away can now be better utilized.